(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
It has been demonstrated that the adenosine deaminase of homogeneous solutions of rat’s organs is subject to inactivation under the influence of bivalent metals (Ca2+, Cu2+, Mg2+), even though different levels of sensitivity to these metals are shown. Maximum inhibitory effect has been observed when adding Cu2+ ions to the environment.